2020
DOI: 10.3390/e22090961
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Modeling and Fractal Dimension Description of Urban Morphology

Abstract: The conventional mathematical methods are based on characteristic length, while urban form has no characteristic length in many aspects. Urban area is a scale-dependence measure, which indicates the scale-free distribution of urban patterns. Thus, the urban description based on characteristic lengths should be replaced by urban characterization based on scaling. Fractal geometry is one powerful tool for the scaling analysis of cities. Fractal parameters can be defined by entropy and correlation functions. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The urban land-cover fractal study is based on the following theoretical assumptions [43]: To measure urban land cover by certain r scale, there is a measure M in the corresponding scale, when the scale r is changed, the measure M(r) is also changed, which can be described as Equation ( 2)…”
Section: Fractal Measurementmentioning
confidence: 99%
“…The urban land-cover fractal study is based on the following theoretical assumptions [43]: To measure urban land cover by certain r scale, there is a measure M in the corresponding scale, when the scale r is changed, the measure M(r) is also changed, which can be described as Equation ( 2)…”
Section: Fractal Measurementmentioning
confidence: 99%
“…The box-counting method was applied on various data forms extracted from urban environments including points, lines and 2D images or 3D models by tracing or converting data from one form to another. A recent review conducted by Chen [18] reaffirmed the relevance of using fractal geometry to analyse urban landscapes and indicated that a 2D analysis was more appropriate for urban analysis as it was simpler and more ef-fective. However, exponential technological advancements now allow the production of increasingly realistic digital surrogates [61].…”
Section: New Approaches To Estimating the Fractal Dimensionmentioning
confidence: 99%
“…Qin et al [17] developed a three-dimensional box-counting method to estimate the fractal dimension of urban form change using remote sensing images. Chen [18] explained cities as pre-fractals rather than real fractals as they have a limited hierarchy, indicating a fractal-like geometric form.…”
Section: Fractal Analysis Of Built Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The irregularity of a fractal set can be computed using the fractal dimension. The fractal dimension is now widely utilized in computer vision applications such as texture analysis [ 2 ], image segmentation [ 3 ], shape recognition [ 4 ], pattern recognition [ 5 ], time series analysis [ 6 ], complex network analysis [ 7 ], landslide susceptibility assessment [ 8 ], topography analysis of thin films [ 9 ], cement-based materials analysis [ 10 ], and description of urban morphology [ 11 ].…”
Section: Introductionmentioning
confidence: 99%